Comparison of Phenolic and Flavonoid Content and Antioxidant and Chelating Activities of Rhizophora mangle in Different Anthropogenically-Polluted Coastal Lagoons - González-Ocampo, Héctor Abelardo; Martínez-Álvarez, Iván Guadalupe; Jaramillo-Flores, María Eugenia; Luna-González, Antonio (Frontiers in Marine Science, 2022)
The production of total phenolic content (TPC) and total flavonoid content (TFC), antioxidant (AA), and copper chelating (CACu+) activities of Rhizophora mangle from three coastal lagoons under different grades of anthropogenic pollution and pollutant presence were analyzed. R. mangle is a mangrove plant that inhabits tropical coastal lagoons and shows the ability to accumulate pollutants in their tissues and respond to environmental stressors via the production of secondary metabolites AA and CACu+ activities. In total, 108 samples (June 2010 to August 2011) of leaves, barks, and the roots of R. mangle from Magdalena Bay (MBAY), Navachiste Lagoon (NLAG), and Terminos Lagoon (TLAG) (Mexico) were collected. Folin-Ciocalteu colorimetric, aluminum chloride colorimetric, ABTS∙+ discoloration, and pyrocatechol-violet methods calculated TPC, TFC, AA, and, CACu+, respectively. Atomic absorption spectrometry, gas chromatography, and Walkley–Black methods were used to calculate the metal content, organochlorine pesticides (OCPs), and organic matter (OM) in sediments. One-way ANOVA and post hoc Tukey’s, Scheffé’s, and Bonferroni and Holm multiple comparisons were used to determine significance, and Pearson’s test was applied to determine the coefficient of correlations. Significant differences among the lagoons of TPC, TFC, AA, and Cu+CA activities of Rhizophora mangle are explained by their different grades and type of anthropogenic pollution. A significant increase in the TPC and TFC in bark implies a response to the metal and OCPs pollution in surrounding sediments. Significant AA and Cu+CA activities responded to combat environmental stress conditions caused by the OCP and trace metal concentrations in surrounding sediments. Strong and positive correlations among OCP and trace metal were found and related to the constant pesticide residues input. However, OCP concentrations in the surrounding sediments of R. mangle trees did not influence the phenolic production of AA or the Cu+ CA. R. mangle is affected by the type of anthropogenic pollutants and was reflected in the bio-compounds production, antioxidant, and chelating activities related to the concentration of the metals in sediments.